Formation and relaxation of RbHe exciplexes on He nanodroplets studied by femtosecond pump and picosecond probe spectroscopy - Giese, Christoph; Mullins, Terry; Weidemüller, Matthias (The journal of chemical physics, 2012)
Vibrationally resolved photoionization spectra of RbHe exciplexes forming on He nanodroplets are recorded using femtosecond pump-probe spectroscopy with amplitude-shaped probe pulses. The time-evolution of the spectra reveals an exciplex formation time ∼10 ps followed by vibrational relaxation extending up to ≳ 1 ns. This points to an indirect, time-delayed desorption process of RbHe off the He surface.